The antenatal urinary tract dilation classification system accurately predicts severity of kidney and urinary tract abnormalities. Issue 5 (October 2017) - Kaspar, C.D.W.; Lo, M.; Bunchman, T.E.; Xiao, N.
Summary: Background: Urinary tract dilation (UTD) is a commonly diagnosed prenatal condition; however, it is currently unknown which features lead to benign and resolving or pathologic abnormalities. A consensus UTD classification system (antenatal UTD classification, UTD-A) was created by Nguyen et al. in 2014 [1], but has not yet been validated. Objective: To evaluate the ability of the UTD-A system to identify kidney and urinary tract (KUT) abnormalities, assess whether UTD-A can predict severity of KUT conditions, and perform a cost analysis of screening ultrasound (US). Methods: A retrospective single-center study was conducted at an academic medical center. Inclusion criteria were: neonates in the well or sick nursery who had a complete abdominal or limited renal US performed in the first 30 days of life between January 01, 2011 and December 31, 2013. Data were collected on prenatal US characteristics from which UTD-A classification was retrospectively applied, and postnatal data were collected up to 2 years following birth. Results: A total of 203 patients were identified. Of the 36 abnormal postnatal KUT diagnoses, 90% were identified prenatally as UTD A1 or UTD A2-3. The remaining 10% developed postnatal KUT abnormalities due to myelomeningocele, such as VUR or UTD, which were not evident prenatally. Overall sensitivity and specificity of the UTD-A system was 0.767 (95% CI 0.577, 0.901) and 0.836 (95% CI 0.758, 0.897), respectively, when resolved UTD was counted as a normal diagnosis. Postnatal diagnoses differed by UTD-A classification as shown in the Summary fig. Of all the obstructive uropathies, 90.9% occurred in the UTD A2-3 class and none occurred in UTD-A Normal. Rate of postnatally resolved UTD was significantly higher in the UTD A1 group (78%) compared with UTD A2-3 (31%) or UTD-A Normal (12%, all P < 0.001). There was a notable trend towards more UT surgeries, UTI, and positive VUR among UTD A2-3 patients, but statistical significance was limited by a small number of patients. Conclusions: This study found that the UTD-A classification system revealed important differences in the severity of UTD abnormalities. With repeated validation in larger cohorts, the UTD-A classification may be used to offer a prognosis for parents regarding prenatally diagnosed KUT conditions. Larger prospective studies should be designed to validate whether the UTD-A system can predict postnatal events related to UTD morbidity such as need for UT-related surgery or UTI. Summary Fig Distribution of postnatal diagnoses by the indication for postnatal ultrasound. KUT, kidney and urinary tract; MCDK, multicystic dysplastic kidney; UTD, urinary tract dilation.